(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: The COVID-19 has overwhelmed health systems across the countries globally. This pandemic has also impacted health related rehabilitation services worldwide which is particularly profound in low and middle-income countries including Bangladesh. Methods: Information used in the study gathered from World Health Organization (WHO) Bangladesh Director General of Health Services (DGHS), Institute of Epidemiology Disease Control and Research (IEDCR), online literature search using PubMed and PubMed Central research engines. Information also collected over personal telephone and email correspondence from the selected government, public, corporate, non-government institutes, and rehabilitation personals during the period of March-May 2020. Gathered data were analyzed; a set of challenges identified, and recommendations were made for a safe and standard working rehabilitation environment in the altered COVID-19 situation. Results: Rehabilitation doctors and therapists at most of the public and private institutes are dedicated to COVID-19 services as per the local administrative directives keeping routine rehabilitation services apart. Few rehabilitation workforces to continue team works, environmental hygiene maintenance and space crisis at service outlets were the major challenges. Specially arranged virtual OPD and telerehabilitation services opened to minimize the rehabilitation burden and sufferings of the patient during the COVID-19 pandemic lock down restriction period. Conclusion: COVID-19 seriously impacted the overall schedule of rehabilitation services. Rehabilitation must be recognized as an un-omissible part of COVID-19 management which requires a planned accommodative working environment in the altered situation within the health care system. Recommendations are provided to keep this pandemic contained while providing adequate and standard rehabilitation services to the disabled in the safe environment in line with WHO rehabilitation 2030. J Bangladesh Coll Phys Surg 2020; 38(0): 76-81